Vulnerability Detection System (Xposed) - Nurin Azyyati, Kamilizahri (2023)
As the world becomes increasingly digitized, software systems have become a primary target for cyber attackers. With the proliferation of new technologies and the growing complexity of software systems, the number of vulnerabilities present in these systems has also grown. These vulnerabilities can range from simple coding errors to more complex architectural flaws, and they can have serious consequences for organizations and individuals alike. To combat this growing threat, it is essential to develop effective vulnerability detection systems that can quickly and accurately identify and classify security risks in software systems. XPOSED Vulnerability Detection System, developed as a final year project, employs scanning techniques to detect and classify vulnerabilities in software systems, thereby assisting organizations in preventing cyber-attacks and safeguarding their essential assets.